Visualisation of gene expression within the context of tissues using an X-ray computed tomography-based multimodal approach - Kairišs, Kristaps; Sokolova, Natalia; Zilova, Lucie; Schlagheck, Christina; Reinhardt, Robert; Baumbach, Tilo; Faragó, Tomáš; Kamp, Thomas van de; Wittbrodt, Joachim; Weinhardt, Venera (Scientific reports, 2024)
The development of an organism is orchestrated by the spatial and temporal expression of genes. Accurate visualisation of gene expression patterns in the context of the surrounding tissues offers a glimpse into the mechanisms that drive morphogenesis. We developed correlative light-sheet fluorescence microscopy and X-ray computed tomography approach to map gene expression patterns to the whole organism`s 3D anatomy. We show that this multimodal approach is applicable to gene expression visualized by protein-specific antibodies and fluorescence RNA in situ hybridisation offering a detailed understanding of individual phenotypic variations in model organisms. Furthermore, the approach offers a unique possibility to identify tissues together with their 3D cellular and molecular composition in anatomically less-defined in vitro models, such as organoids. We anticipate that the visual and quantitative insights into the 3D distribution of gene expression within tissue architecture, by multimodal approach developed here, will be equally valuable for reference atlases of model organisms development, as well as for comprehensive screens, and morphogenesis studies of in vitro models.
Gesehen am 21.10.2024